2015
DOI: 10.1021/acs.jafc.5b04575
|View full text |Cite
|
Sign up to set email alerts
|

Root Glucosinolate Profiles for Screening of Radish (Raphanus sativus L.) Genetic Resources

Abstract: Radish (Raphanus sativus L.), a root vegetable, is rich in glucosinolates (GLs), which are beneficial secondary metabolites for human health. To investigate the genetic variations in GL content in radish roots and the relationship with other root phenotypes, we analyzed 71 accessions from 23 different countries for GLs using HPLC. The most abundant GL in radish roots was glucoraphasatin, a GL with four-carbon aliphatic side chain. The content of glucoraphasatin represented at least 84.5% of the total GL conten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
48
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 48 publications
(54 citation statements)
references
References 28 publications
5
48
1
Order By: Relevance
“…For example, in radish, it has consistently been reported that the majority GLS is glucoraphasatin; however, the raphasatin levels found when the ITC profile was studied, were negligible or non-quantifiable because of the extraction conditions and the hydrolysis affecting the results, especially if the medium is polar or aqueous [26]. Furthermore, the ITC profile of each cruciferous species varies according to the cultivar or variety considered and also according to the plant tissue found [27,28]. For example, in rocket leaves, the main ITC generally detected corresponds to sativin [29], but in rocket seeds, the main ITC detected have been erucin and sulforaphane (SFN) [30].…”
Section: Organosulfur Compoundsmentioning
confidence: 99%
“…For example, in radish, it has consistently been reported that the majority GLS is glucoraphasatin; however, the raphasatin levels found when the ITC profile was studied, were negligible or non-quantifiable because of the extraction conditions and the hydrolysis affecting the results, especially if the medium is polar or aqueous [26]. Furthermore, the ITC profile of each cruciferous species varies according to the cultivar or variety considered and also according to the plant tissue found [27,28]. For example, in rocket leaves, the main ITC generally detected corresponds to sativin [29], but in rocket seeds, the main ITC detected have been erucin and sulforaphane (SFN) [30].…”
Section: Organosulfur Compoundsmentioning
confidence: 99%
“…GSL contents were determined by the purification and desulfation of GSLs (ISO 9167-1:1995/A1:2013) and by applying the desulfo-GSLs analysis method (Yi et al, 2015). Ten milliliters of boiled 70% methanol were added to 200 mg of lyophilized radish root powder and placed in a water bath at 90°C for 30 min, and centrifuged at 6950 Â g for 30 min.…”
Section: Extraction Of Desulfo-gslsmentioning
confidence: 99%
“…Identification of desulfo-GSLs was performed using a Q Exactive Hybrid Quadrupole-Orbitrap instrument (Thermo Scientific Co., USA) equipped with a Dionex Ultimate 3000 UHPLC system (Thermo Scientific Co., USA) (Yi et al, 2015). Ten lL of samples were separated on an INNO 10 column (2.0 Â 100 mm, Young Jin Biochrom, Korea) at a 150 lL/min flow rate and a 35°C column temperature.…”
Section: Identification Of Desulfo-gslsmentioning
confidence: 99%
See 2 more Smart Citations